Use of mobile-app to collect feedback from undergraduate students posted in Community Medicine - Saurabh RamBihariLal Shrivastava; Prateek Saurabh Shrivastava (Al Ameen Medical College, 2019)
Amidst the rising trends of the use of internet in mobile devices, e-learning has started to find its feet in the delivery of medical education in an innovative, yet needed way [1]. For many years, the internet has been used predominantly in the data analysis collected from different locations, but then due to the development of mobile-based apps even for the data collection activity, the entire field of research has been revolutionized [1-2]. The adoption of such an approach not only saves paper, but even gives the administrators' a real-time access to the collected data, which subsequently expedites even the analysis aspect [1-2].